PENDIDIKAN DAN LITERASI MASYARAKAT: PENINGKATAN KUALITAS PENDIDIKAN MELALUI SOSIALISASI PENTINGNYA PENDIDIKAN, PELATIHAN LITERASI DASAR DAN PENDAMPINGAN BELAJAR BAGI ANAK - Tangkelallo, Dian Intan; Mantong, Agustinus; Pakabu, Herman (Yayasan Education and Social Center, 2025)
Community education and literacy are essential foundations for developing high-quality human resources. This program aims to enhance educational quality through three main strategies: raising awareness of the importance of education, providing basic literacy training, and offering learning assistance for children. Awareness campaigns focus on engaging parents and communities to recognize education's role in improving welfare. Basic literacy training emphasizes reading, writing, and arithmetic as fundamental skills for children. Meanwhile, learning assistance provides direct support to help students overcome learning difficulties and improve motivation. The methods applied include interactive lectures, hands-on practice, and personalized guidance. The results indicate increased public understanding of the importance of education, improved children’s literacy skills, and the development of more positive study habits. This program is expected to serve as a sustainable model for empowering communities through education and literacy.